Retraction Notice for "Knowledge on Pre-conception Care among Reproductive Age Women" - Board, Editorial (Journal of Advanced Academic Research, 2022)
On 19th April 2022 the Editorial Board of the Journal of Advanced Academic Research agreed to retract the article ‘Knowledge on Pre-conception Care among Reproductive Age Women’ published in the Journal of Advanced Academic Research, Vol.9(1) pages 13-20 (DOI: https://doi.org/10.3126/jaar.v9i1.44040 ) ) as it was found to be the same as the article ‘Knowledge on Pre-conception Care among Reproductive Age Women’ published in the Saudi Journal of Medical and Pharmaceutical Sciences, Vol.2(1) pages 1-6, http://scholarsmepub.com/wp-content/uploads/2016/02/SJMPS-211-6.pdf